Astrocytes are necessary for blood–brain barrier maintenance in the adult mouse brain. Issue 2 (21st September 2020) - Heithoff, Benjamin P.; George, Kijana K.; Phares, Aubrey N.; Zuidhoek, Ivan A.; Munoz‐Ballester, Carmen; Robel, Stefanie
Abstract: In the adult brain, multiple cell types are known to produce factors that regulate blood–brain barrier (BBB) properties, including astrocytes. Yet several recent studies disputed a role for mature astrocytes at the BBB. To determine if astrocytes contribute a nonredundant and necessary function in maintaining the adult BBB, we used a mouse model of tamoxifen‐inducible astrocyte ablation. In adult mice, tamoxifen induction caused sparse apoptotic astrocyte cell death within 2 hr. Indicative of BBB damage, leakage of the small molecule Cadaverine, and the large plasma protein fibrinogen into the brain parenchyma indicative of BBB damage was detected as early as astrocyte ablation was present. Vessels within and close to regions of astrocyte loss had lower expression of the tight junction protein zonula occludens‐1 while endothelial glucose transporter 1 expression was undisturbed. Cadaverine leakage persisted for several weeks suggesting a lack of barrier repair. This is consistent with the finding that ablated astrocytes were not replaced. Adjacent astrocytes responded with partial nonproliferative astrogliosis, characterized by morphological changes and delayed phosphorylation of STAT3, which restricted dye leakage to the brain and vessel surface areas lacking coverage by astrocytes 1 month after ablation. In conclusion, astrocytes are necessary to maintain BBB integrity in the adult brain. BBB‐regulating factors secreted by other cell types, such as pericytes, are not sufficient to compensate for astrocyte loss. Main Points: Mature astrocytes are necessary for maintenance of endothelial tight junctions in the adult brain. Ablated astrocytes are not replaced by proliferation or process extension of neighboring astrocytes, resulting in longterm blood‐brain barrier damage.